Kinetics of HIV-1 CTL epitopes recognized by HLA I alleles in HIV-infected individuals at times near primary infection: the Provir/Latitude45 study. - Jennifer Papuchon; Patricia Pinson; Gwenda-Line Guidicelli; Pantxika Bellecave; Réjean Thomas; Roger LeBlanc; Sandrine Reigadas; Jean-Luc Taupin; Jean Guy Baril; Jean Pierre Routy; Mark Wainberg; Hervé Fleury; et al. (PLoS ONE, 2014)
In patients responding successfully to ART, the next therapeutic step is viral cure. An interesting strategy is antiviral vaccination, particularly involving CD8 T cell epitopes. However, attempts at vaccination are dependent on the immunogenetic background of individuals. The Provir/Latitude 45 project aims to investigate which CTL epitopes in proviral HIV-1 will be recognized by the immune system when HLA alleles are taken into consideration. A prior study (Papuchon et al, PLoS ONE 2013) showed that chronically-infected patients under successful ART exhibited variations of proviral CTL epitopes compared to a reference viral strain (HXB2) and that a generic vaccine may not be efficient. Here, we investigated viral and/or proviral CTL epitopes at different time points in recently infected individuals of the Canadian primary HIV infection cohort and assessed the affinity of these epitopes for HLA alleles during the study period. An analysis of the results confirms that it is not possible to fully predict which epitopes will be recognized by the HLA alleles of the patients if the reference sequences and epitopes are taken as the basis of simulation. Epitopes may be seen to vary in circulating RNA and proviral DNA. Despite this confirmation, the overall variability of the epitopes was low in these patients who are temporally close to primary infection.